The mechanism for adsorption of Cr(VI) ions by PE microplastics in ternary system of natural water environment. (February 2020) - Zhang, Wei; Zhang, Liying; Hua, Tian; Li, Yonggan; Zhou, Xing; Wang, Wenxia; You, Zhangchao; Wang, Huiliang; Li, Mengjia
Abstract: More attention was paid to the attachment between microplastics and environmental pollutants. The adsorption performance of Polyethylene (PE) beads (a typical type of microplastics) and Cr(VI) ions with the existence of sodium dodecyl benzene sulfonate (SDBS) was investigated in this paper. The adsorption experiments of Cr(VI) ions by PE microplastics were conducted at different conditions, i.e. PE doses, pH and SDBS concentrations, respectively. The adsorption capability of Cr(VI) ions was increased from 0.39 to 1.36 mg⋅g −1 when the dosage of PE microplastics was increased from 2 to 14 g ⋅L −1 at pH of 5 with addition of SDBS, compared with increasing adsorption capability from 0.03 to 0.32 mg⋅g −1 without addition of SDBS. The pH would influence the adsorption capability with and without the addition of SDBS. When the pH was less than 6, the adsorption capability of Cr(VI) would be promoted by the addition of SDBS; however, there was a contrast tendency when the pH was more than 6, which was attributed to that SDBS would compete with CrO4 2− for occupying the adsorption sites of PE microplastic. The SDBS concentration would affect the adsorption performance of Cr(VI) ions onto PE microplastics. The peak of the adsorption capacity was at SDBS concentration between 1 and 1.5 mM. This research would provide a basis for investigating the influence of SDBS on adsorption performance of heavy metal by PE microplastics to simulate the surface attachment model of those three kinds of pollutants. Graphical abstract: Image 1 Highlights: The adsorption of Cr(VI) ions by PE microplastics in ternary systems was simulated. SDBS could increase the interaction between PE and Cr(VI) ions. The pH of the solution and SDBS concentration would significantly influence the adsorption of Cr(VI) by PE beads. The peak of the adsorption capacity was at SDBS concentration between 1 and 1.5 mM.